2019
DOI: 10.32872/spb.v14i3.30091
|View full text |Cite
|
Sign up to set email alerts
|

Can Virtual Observers Affect Our Behavior? Social Facilitation in Virtual Environments: A Mini-Review

Abstract: The social facilitation effect describes the change in the performance of the task under the influence of the presence of observers. The effect itself consists of two components: social facilitation in simple tasks and social inhibition in complex tasks. In the context of the dynamic development of new technologies, the question of the possible influence on human behavior by virtual characters gains importance. We attempted to critically describe and summarize current research on social facilitation in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This investigation expands the latter work by testing for previously validated SFE/SIE mechanisms (i.e., evaluation apprehension, mere effort, and attentional conflict), as well as people's mind perception in robots as an ostensible precondition. Acknowledging mixed findings for digital observers (Sterna et al, 2019) and methodological criticism (Irfan et al, 2018), this study followed suggested procedures for SFE/SIE studies to minimize the influence of confounds (i.e., using a welltested task and a pretested robot, controlling for observer behavior and positioning, isolating the observer's influence) and, in doing so, addressed why previous findings may have been inconsistent. Our findings, overall, indicated no significant differences in SFE/SIE across observer conditions, no significant differences in SFE/SIE mechanisms, and only a single statistically meaningful effect of mind perception (i.e., improved performance corresponding with perceptions of basic agentic capacities).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This investigation expands the latter work by testing for previously validated SFE/SIE mechanisms (i.e., evaluation apprehension, mere effort, and attentional conflict), as well as people's mind perception in robots as an ostensible precondition. Acknowledging mixed findings for digital observers (Sterna et al, 2019) and methodological criticism (Irfan et al, 2018), this study followed suggested procedures for SFE/SIE studies to minimize the influence of confounds (i.e., using a welltested task and a pretested robot, controlling for observer behavior and positioning, isolating the observer's influence) and, in doing so, addressed why previous findings may have been inconsistent. Our findings, overall, indicated no significant differences in SFE/SIE across observer conditions, no significant differences in SFE/SIE mechanisms, and only a single statistically meaningful effect of mind perception (i.e., improved performance corresponding with perceptions of basic agentic capacities).…”
Section: Discussionmentioning
confidence: 99%
“…Although these findings suggest that SFE/SIE may manifest for robot observers, Irfan et al (2018) advocated against such a conceptual transfer. They argued that (a) people's participation in a study in which researchers (copresent or not) intend to evaluate them defies a clear attribution of any effects to the observing agent and (b) previous studies failed to replicate SFE/SIE with digital agents (e.g., Hertz & Wiese, 2017), alongside (c) general inconsistency in such effects (Sterna et al, 2019). Beyond that general conceptual challenge, we also note that the supportive studies have been subject to methodological limitations.…”
Section: Social Facilitation/inhibition Effects With Social Robotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, a specific example of the inability to control for confounders is the lack of pretesting of the stimuli and procedures used in the VR-based social experiments. As Emmerich and Masuch (2016) point out, lack of pretesting is one of the problems connected to the research in VR conducted with virtual characters (for discussion: Sterna et al, 2019). Besides virtual characters, experimental procedures in VR experiments are usually also not pretested, made ad hoc, without the usage of standardized materials or performing pilot tests (with few exceptions, e.g., Garau et al, 2005, p. 107;Zimmer et al, 2019, p. 7-12;Harjunen, 2019, p. 34-48;Niu et al, 2020, p. 060413-3).…”
Section: Lack Of Pre-testingmentioning
confidence: 99%
“…With the development of virtual reality (VR) technologies, researchers have begun to explore the impact of computergenerated agents in virtual environments (VEs) on users in terms of the social facilitation effect. Several studies examining this phenomenon in VR have been published, but according to the recent review their results are not consistent (Sterna et al, 2019). To the best of our knowledge, the full social facilitation and inhibition effect in easy and difficult tasks respectively has been shown only once in VR (Park and Catrambone, 2007).…”
Section: Introductionmentioning
confidence: 96%